Implementasi Sistem Penghilang Derau Adaptif Menggunakan Algoritma LMS pada FPGA Altera Flex10KLC84 - Agfianto Eko Putra; Susaf Noor Azhar (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
The Adaptive Noise Cancelling Systemhas been implemented in FPGA’s AlteraFelx10KCL84, chip which has 576 LE and 3 EAB. Thesystem has data communication capability betweenPC and system and the baudrate is 9,600bps. Dataformat using 8-bit data width two’s complementinteger and 8 scale factor. Total resources which hasbeen used is 564 LE and 2 EAB, after optimization.The accuracy is 100% according to the MATLABresults for the same computation equation.Systemrespond for square wave is better then sinusoidalwave.